2016
DOI: 10.1016/j.pharmthera.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Personalized in vitro cancer models to predict therapeutic response: Challenges and a framework for improvement

Abstract: Personalized cancer therapy focuses on characterizing the relevant phenotypes of the patient, as well as the patient’s tumor, to predict the most effective cancer therapy. Historically, these methods have not proven predictive in regards to predicting therapeutic response. Emerging culture platforms are designed to better recapitulate the in vivo environment, thus, there is renewed interest in integrating patient samples into in vitro cancer models to assess therapeutic response. Successful examples of transla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 215 publications
(279 reference statements)
2
65
0
1
Order By: Relevance
“…A major obstacle to studying the mechanisms of drug resistance is that traditional in vitro models poorly recapitulate in vivo biology. Several authors have argued that increasing the physiologic relevance of in vitro platforms may improve the ability to predict drug responses (1,43,44). In support of this, we found that a 2D coculture system did not segregate the anastrazole responses of patients who are lean or obese as did our organotypic culture platform.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…A major obstacle to studying the mechanisms of drug resistance is that traditional in vitro models poorly recapitulate in vivo biology. Several authors have argued that increasing the physiologic relevance of in vitro platforms may improve the ability to predict drug responses (1,43,44). In support of this, we found that a 2D coculture system did not segregate the anastrazole responses of patients who are lean or obese as did our organotypic culture platform.…”
Section: Discussionsupporting
confidence: 75%
“…Approximately two thirds of all breast cancer cases are estrogen receptor (ER) a positive. ER is thought to regulate the progression of ER-positive breast cancer by controlling the growth and death of breast cancer cells through estrogen-regulated signaling (1). In postmenopausal women, treatment of ER-positive breast cancer typically involves directly targeting ERmediated signaling with ER antagonists such as tamoxifen, or indirectly limiting local estrogen by suppressing the conversion of testosterone (T) to E 2 with the use of aromatase inhibitors such as anastrazole (2).…”
mentioning
confidence: 99%
“…Indeed there is increasing evidence that inflammation and metabolic abnormalities within the cancer microenvironment are not simply a passive reaction to cancer cells, but can also drive neoplastic transformation (23,24). This knowledge is beginning to be translated into clinical applications in the development of personalized chemotherapeutic regimens based on in vitro testing incorporating elements of the patient's tumor microenvironment (25). This new understanding is also shaping primary prevention strategies that promote a cancer-resistant extracellular environment, such as aspirin for colon cancer and metformin for breast cancer (26,27).…”
Section: Importance Of Connective Tissue In Cancer Biologymentioning
confidence: 99%
“…One approach to developing new tools to guide individualized treatment selection utilizes chemotherapy sensitivity and resistance assays (CSRAs) which use viable tissue from a tumor to provide predictive information about response to treatment (Burstein et al, 2011;Morgan et al, 2016). These techniques have the bene t of being inexpensive, quick and compatible with high-throughput screening to help guide treatment decision making (Morgan et al, 2016). Initially, assays were developed using cells from tumors in two dimensional (2D) tissue culture (Joo et al, 2009;Ochs et al, 2005).…”
Section: Introductionmentioning
confidence: 99%